Acute Onset Collagenous Colitis with Unique Endoscopic Findings. (24th December 2014) - Moroi, Rintaro; Endo, Katsuya; Kuhroha, Masatake; Shiga, Hisashi; Kakuta, Yoichi; Kinouchi, Yoshitaka; Shimosegawa, Tooru
Abstract : We experienced a rare case of 72-year-old woman with acute onset collagenous colitis (CC) induced by lansoprazole. The patient developed acute abdominal pain, watery diarrhea, and melena that are quite rare in usual CC. We could find the characteristic colonoscopic findings such as active long liner ulcers in the patient. We also observed the healing courses of these unique findings. Our case indicates two important points of view. (1) CC sometimes develops with acute onset symptoms which resemble those of ischemic colitis. (2) Colonoscopy would be useful and necessary to distinguish acute onset CC and ischemic colitis.